Community-acquired meningoencephalitis due to concomitant infection caused by Naegleria fowleri and Streptococcus pneumoniae from Karachi, Pakistan- A Case Report - Najia Karim Ghanchi; Safia Bibi; Binish Arif Sultan; Afia Zafar (Journal of the Pakistan Medical Association, 2023)
Naegleria fowleri causes acute fatal primary amoebic meningoencephalitis in adults and children with a history of exposure to aquatic activities. However, several cases of Primary Amoebic Meningoencephalitis (PAM) have been reported from Karachi with no history of aquatic recreational activities suggesting the presence of N. fowleri in domestic water. This study reports a case of co-infection of N. fowleri with Streptococcus pneumoniae in an elderly hypertensive male. Keywords: Naegleria fowleri. PAM, Streptococcus pneumoniae.